Práticas educativas e escolarização de alunos com transtorno do espectro autista na educação profissional - Simone Pinto Vasconcellos (2019)
Since the 1990s, public policies and educational legislation in Brazil have advocated education as a fundamental and universal right, ensuring to the target public of special education, access, permanence, participation and learning in common classes of regular schools, in accordance with international declarations. Considering this context, this research has as general objective to analyze the educational practices adopted in the schooling of a student with Autism Spectrum Disorder (ASD) in the Integrated Technical Education based on the perception of this young student, his parents and the teachers involved in this process. The specific objectives were to analyze the educational practices adopted in the educational course of the student with autism in the Integrated Technical Education and to identify the perceptions of the student, his parents and their teachers about these practices of the schooling. The study was guided by a qualitative approach, as a case study. To collect the data, were executed a documentary research and semi-structured interviews with the student with ASD, his parents and the teachers who taught to the student in the institution of the State Center for Technical Education, located in the metropolitan region of Belo Horizonte (Minas Gerais). The data were analyzed using the Content Analysis Method, described by Bardin, and also the theoretical contribution of inclusive education and the literature on ASD. The results of this research point to the low enrollment of people with autism in the Integrated Technical Education and to the effectiveness of educational practices that involve collaborative work among educators, in interaction with the family, support actions to the student, flexibilization of curricular temporality, adjustments to assessments, didactic procedures and specific teaching proposals. In general, these practices have resulted in more adequate conditions of schooling for the student with autism. However, the data analysis indicates challenges to be overcome, related to the lack of knowledge of educators and the need for institutionalization of guidelines and educational actions for an professional education accessible to all students.